HOUSEHOLD SOLID WASTE AND URBAN COLLECTION: SOCIAL PERCEPTION AND MANAGEMENT CHALLENGES IN A CITY IN MARANHÃO - Ribeiro dos Santos Neta, Elza; Kellen Mota Bezerra, Luana (Revista Gênero e Interdisciplinaridade, 2026)
The intensification of urbanization and consumption patterns has significantly increased the generation of urban solid waste, becoming one of the main socio-environmental challenges for Brazilian cities. In this context, this study aims to analyze the management of domestic solid waste in the municipality of Imperatriz-MA, with emphasis on collection, final disposal, and the population’s perception of these practices. Methodologically, the research is characterized as a qualitative-quantitative study, with a descriptive and exploratory approach, based on bibliographic and documentary research, combined with the application of a structured questionnaire to 52 residents from different neighborhoods of the municipality. The data were analyzed using descriptive statistics and interpreted in light of current environmental legislation and the theoretical framework. The results show that, although most respondents claim to have knowledge about solid waste and selective collection, this knowledge is superficial and ineffective in daily practice, reflecting weaknesses in environmental education and social participation. Significant ignorance was also found regarding the final destination of waste, the functioning of the sanitary landfill, and the environmental impacts associated with improper disposal. It is concluded that the problem of solid waste in Imperatriz is related not only to collection, but also to the absence of structured public policies, continuous environmental education, and mechanisms that promote shared responsibility between public authorities and society.